DISEASES OF THE DIGESTIVE SYSTEM AND THEIR RISK FACTORS - Shaymardanov Bakhtiyor; Avezova Guloyim Sattarovna (Scholar Express Journals, 2024)
This article provides information about diseases of the digestive system , the main causes of disorders of the digestive process, and the actions to be taken to prevent diseases of the digestive system
Keywords: digestive system; stomach; oral cavity; small intestine